NIMG-61. CLINICAL UTILITY OF SOMATOSTATIN RECEPTOR PET IMAGING BIOMARKERS FOR CHARACTERIZATION OF MENINGIOMA AMONG INCIDENTAL CNS LESIONS. (12th November 2021) - Ensign, Shannon Fortin; Argarwal, Muskan; Badawy, Mohamed; Halfdanarson, Thorvardur; Johnson, Derek; Sonbol, Mohamad (Bassam); Kendi, Ayse
Abstract: BACKGROUND: Somatostatin receptor (SSTR) PET/CT is utilized with increasing frequency in the clinical treatment of neuroendocrine tumors. Incidental CNS lesions are commonly noted and presumed to be meningiomas, however 68 Gallium (Ga-68)-DOTATATE radionuclide use lacks specificity for meningioma identification. Currently there is no established SSTR-based imaging criteria for classification of incidental CNS lesions. METHODS: We retrospectively analyzed patients across clinical and radiological databases at Mayo Clinic who had undergone both Ga-68-DOTATATE PET/CT and brain MR imaging who had an incidental CNS lesion identified with clinical or radiographic prediction of meningioma. Known meningioma diagnoses prior to imaging were excluded. Imaging indication, semi-quantitative measures, and corresponding clinical history were analyzed to identify metrics impacting both the predictive and descriptive utility of SSTR-based imaging as compared to corresponding MRI prediction in incidental CNS lesions. RESULTS: Among 59 patients with a CNS lesion identified on both imaging modalities, most scans were performed for a history of neuroendocrine tumor (71%). Cases with concordant lesion type prediction of meningioma between imaging modalities (N = 25) displayed a higher median SUV max and Krenning score on Ga-68-DOTATATE PET compared to cases with concordant prediction of other lesions (N=10) or discordant prediction of meningioma (N=24). Ga-68-DOTATATE was more likely to discordantly predict meningioma as compared to the corresponding patient MRI in cases with lower SUV max values. The addition of Qclear technology was significantly associated with diagnostic clarification in cases of imaging discordant tumor type prediction. Prior cranial radiation or use of a somatostatin mimetic did not affect quantitative radiographic measures in lesion characterization, and MRI-based tumor size was similar across groups. CONCLUSION: The continued development of SSTR-based imaging biomarker signatures across incidental CNS lesion subtypes will further define the role of this imaging modality in the clinical diagnosis and management of presumed meningiomas.